APPROACHING ROAD INFRASTRUCTURE VULNERABILITY FROM A MOBILITY MANAGEMENT PERSPECTIVE. A 5 YEAR ANALYSIS OF ACCIDENT DYNAMICS IN BRASOV COUNTY - Ciprian Sorin VLAD; Iulia Ioana MIRCEA; Larisa IVASCU; Eugen ROȘCA (Annals: Series on engineering sciences (Academy of Romanian Scientists))
Recorded fatalities as a result of road accidents place Romania at the top of the European countries with the most worrying statistics, situating the mobility management in a deficient position, often motivated by the vulnerability of the road infrastructure. The present paper, conducted with the statistics provided by the Romanian Police, analyzes the impact of road quality on the occurrence of accidents in determining the severity of injuries to participants. This study was carried out over a period of 5 years in Brasov County.